anonymous
  • anonymous
2x^2-4x-18=0 Complete the square
Mathematics
  • Stacey Warren - Expert brainly.com
Hey! We 've verified this expert answer for you, click below to unlock the details :)
SOLVED
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
chestercat
  • chestercat
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
mathstudent55
  • mathstudent55
1. Add 18 to both sides to get the -18 term on the right side.
mathstudent55
  • mathstudent55
2. You must have x^2 as the first term, so divide both sides by 2. Do these two steps and show what you got.
Luigi0210
  • Luigi0210
Go!

Looking for something else?

Not the answer you are looking for? Search for more explanations.

More answers

anonymous
  • anonymous
Simplifying 2x2 + 4x + -18 = 0 Reorder the terms: -18 + 4x + 2x2 = 0 Solving -18 + 4x + 2x2 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), '2'. 2(-9 + 2x + x2) = 0 Ignore the factor 2. Subproblem 1 Set the factor '(-9 + 2x + x2)' equal to zero and attempt to solve: Simplifying -9 + 2x + x2 = 0 Solving -9 + 2x + x2 = 0 Begin completing the square. Move the constant term to the right: Add '9' to each side of the equation. -9 + 2x + 9 + x2 = 0 + 9 Reorder the terms: -9 + 9 + 2x + x2 = 0 + 9 Combine like terms: -9 + 9 = 0 0 + 2x + x2 = 0 + 9 2x + x2 = 0 + 9 Combine like terms: 0 + 9 = 9 2x + x2 = 9 The x term is 2x. Take half its coefficient (1). Square it (1) and add it to both sides. Add '1' to each side of the equation. 2x + 1 + x2 = 9 + 1 Reorder the terms: 1 + 2x + x2 = 9 + 1 Combine like terms: 9 + 1 = 10 1 + 2x + x2 = 10 Factor a perfect square on the left side: (x + 1)(x + 1) = 10 Calculate the square root of the right side: 3.16227766 Break this problem into two subproblems by setting (x + 1) equal to 3.16227766 and -3.16227766. Subproblem 1 x + 1 = 3.16227766 Simplifying x + 1 = 3.16227766 Reorder the terms: 1 + x = 3.16227766 Solving 1 + x = 3.16227766 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + x = 3.16227766 + -1 Combine like terms: 1 + -1 = 0 0 + x = 3.16227766 + -1 x = 3.16227766 + -1 Combine like terms: 3.16227766 + -1 = 2.16227766 x = 2.16227766 Simplifying x = 2.16227766 Subproblem 2 x + 1 = -3.16227766 Simplifying x + 1 = -3.16227766 Reorder the terms: 1 + x = -3.16227766 Solving 1 + x = -3.16227766 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + x = -3.16227766 + -1 Combine like terms: 1 + -1 = 0 0 + x = -3.16227766 + -1 x = -3.16227766 + -1 Combine like terms: -3.16227766 + -1 = -4.16227766 x = -4.16227766 Simplifying x = -4.16227766 Solution The solution to the problem is based on the solutions from the subproblems. x = {2.16227766, -4.16227766} Solution x = {2.16227766, -4.16227766}

Looking for something else?

Not the answer you are looking for? Search for more explanations.